Analysis of the association between osteoporosis and muscle strength in Korean adults: a national cross-sectional study - Ji-Young Choi; Young-Mo Yang (BMC, 2023)
Abstract Background This study aimed to examine the associations between osteoporosis and hand grip strength (HGS), a surrogate marker of muscular strength, among Korean adults stratified by body mass index (BMI), age, and renal function. Methods This study was conducted using the data obtained from the Korea National Health and Nutrition Examination Survey 2015-2019, a cross-sectional and nationally representative survey performed by the Korea Centers for Diseases Control and Prevention. Results Of the 26,855 subjects included in this study, those with low muscle strength (LMS) and normal muscle strength were showed in 4,135 (15.4%) and 22,720 (84.6%) subjects, respectively. The osteoporotic subjects had a higher prevalence rate for LMS than those without osteoporosis after adjusting for age [odds ratio (OR), 1.684; 95% confidence interval (CI), 1.500-1.890). The subjects with osteoporosis and BMI < 18.5 kg/m2 also had a higher prevalence rate for LMS after adjusting for age compared to those with non-osteoporosis and BMI < 18.5 kg/m2 (OR, 1.872; 95% CI, 1.043-3.359). Compared to the non-osteoporotic subjects with estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73 m2, those with osteoporosis and eGFR ≥ 60 mL/min/1.73 m2 had a higher prevalence rate for LMS after controlling for age and sex (OR, 1.630; 95% CI, 1.427-1.862). Conclusions The results showed that osteoporosis was likely to contribute to an increased prevalence rate of LMS in terms of HGS. Aging, BMI, and renal function also had significant effects on the association between osteoporosis and LMS. This association is likely to assist in developing better strategies to estimate bone health in clinical or public health practice.